2007
DOI: 10.1097/01.nor.0000300946.86708.bc
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in the Orthopaedic Patient

Abstract: Published incidence of delirium in orthopaedic patients ranges from 5.1% to 61%. Delirium may present before or after the patient undergoes the surgical procedure and has demonstrated increased risk, including mortality. Yet, delirium goes unrecognized by both physicians and nurses. This article focuses on the literature on delirium in the orthopaedic patient, including incidence, how to identify those patients at risk, patient outcomes, nonpharmacological and pharmacological interventions, and provides an exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
9
0
4
Order By: Relevance
“…The authors stressed that it is not enough to provide nurses with the tools and teach them how to use them, but it is imperative to educate nurses on how to interpret the results of these tools so that they may intervene accordingly. Once again the findings of this study agree with the findings of similar studies that suggested that delirium detection increases when nurses receive comprehensive education on delirium and training in the use of a validated screening tool such as CAM (Neitzel et al 2007, Steis & Fick, 2012Waszynski & Petrovic 2008). Although the study contained a random sample of 800 nurses, only 181 responded (22Á62%).…”
Section: Delirium As a Burden Experienced By Nursessupporting
confidence: 88%
See 2 more Smart Citations
“…The authors stressed that it is not enough to provide nurses with the tools and teach them how to use them, but it is imperative to educate nurses on how to interpret the results of these tools so that they may intervene accordingly. Once again the findings of this study agree with the findings of similar studies that suggested that delirium detection increases when nurses receive comprehensive education on delirium and training in the use of a validated screening tool such as CAM (Neitzel et al 2007, Steis & Fick, 2012Waszynski & Petrovic 2008). Although the study contained a random sample of 800 nurses, only 181 responded (22Á62%).…”
Section: Delirium As a Burden Experienced By Nursessupporting
confidence: 88%
“…Once again the findings of this study agree with the findings of similar studies that suggested that delirium detection increases when nurses receive comprehensive education on delirium and training in the use of a validated screening tool such as CAM (Neitzel et al . , Steis & Fick, ; Waszynski & Petrovic ). Although the study contained a random sample of 800 nurses, only 181 responded (22·62%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antipsychotics have been studied extensively in the elderly patient population and should be administered at the lowest adequate dosages 65 . Haloperidol, the most widely studied antipsychotic, is the most frequently used antipsychotic medication for delirium because of its few anticholinergic side effects, few active metabolites, and small likelihood of causing sedation 65‐68 . Most studies have used doses of 0.25 to 0.50 mg haloperidol given every four hours for elderly or seriously medically compromised patients and doses of 2 to 3 mg per day in healthier patients 65,67‐69 .…”
Section: Implementation and Evaluation Designmentioning
confidence: 99%
“…P ostoperative delirium (POD) affects between 9.9% and 67% 1 of older adults undergoing noncardiac surgery and 5.1% and 61% of older adults undergoing orthopedic surgery. 2 POD can have devastating long-term sequelae, such as cognitive dysfunction, decline in functional status, and increased morbidity and mortality. 3,4 Given that there are an estimated 13.6 million surgeries performed annually on patients aged 65 years and older in the United States alone, and approximately 5 million knee and hip replacements, the magnitude of this problem is staggering.…”
mentioning
confidence: 99%